The ABC‐Stroke Risk Score and Effects of Atrial Fibrillation Screening on Stroke Prevention: Results From the Randomized LOOP Study - Lucas Yixi Xing; Søren Zöga Diederichsen; Søren Højberg; Derk W. Krieger; Claus Graff; Ruth Frikke‐Schmidt; Pyotr G. Platonov; Morten S. Olesen; Axel Brandes; Lars Køber; Ketil Jørgen Haugan; Jesper Hastrup Svendsen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background The ABC‐stroke score is a risk scheme for prediction of stroke or systemic embolism (SE) in atrial fibrillation (AF). This study sought to examine whether the score could be useful in predicting stroke in AF‐naïve individuals and risk stratifying for AF screening. Methods and Results The LOOP (Atrial Fibrillation Detected by Continuous ECG Monitoring Using Implantable Loop Recorder to Prevent Stroke in High‐Risk Individuals) study randomized 6004 AF‐naïve individuals aged 70 to 90 years with stroke risk factors to either screening with an implantable loop recorder and anticoagulation upon detection of new‐onset AF episodes ≥6 minutes, or usual care. A total of 5781 participants had available ABC‐stroke score at baseline and were included in this secondary analysis: 4170 (72.1%) with an estimated stroke/SE risk ≤1%/year versus 1611 (27.9%) with an estimated stroke/SE risk >1%/year. Having an annual ABC‐stroke risk >1% was associated with stroke/SE, stroke/SE/cardiovascular death, and all‐cause death (hazard ratio, 1.82 [95% CI, 1.44–2.21], 2.17 [95% CI, 1.80–2.62], and 2.19 [95% CI, 1.87–2.56], respectively). For screening with implantable loop recorder versus usual care, no significant reduction in these study outcomes was obtained in any ABC‐stroke risk groups (P>0.0500 for all), with no signal toward interaction (Pinteraction>0.2500 for all). Similar findings were yielded when assessing the ABC‐stroke score as a continuous variable. Conclusions In an elderly, AF‐naïve population with additional stroke risk factors, a higher ABC‐stroke score could identify individuals with increased stroke risk. However, this risk score may not be useful in pinpointing those more likely to benefit from AF screening and subsequent preventive treatment. These findings should be considered as hypothesis generating and warrant further study. Registration URL: https://www.clinicaltrials.gov; unique identifier: NCT02036450.